Membangun Spiritualitas Dialogal Antariman Umat Katolik dengan Umat Beragama Lain - Thomas Julivadistanto (STIPAS St. Sirilus Ruteng, 2012)
Mission of the church today should and foremost be characterized as an exercise of dialogue.Just as the interior life of God is a perfect communion of gift and reception,identity and openness to the other, communion in relationship and communion in mission, so the church that is called into being by that mission must be a community that not only gives of itself in service to the world and to the peoples of the world,s cultures but learns from its involvement and expands its imagination ot the depths of God unfathomable riches.And just as the ways about persuasion and freedom - respecting love, mission can no longer proceeds in wys that neglect the freedom and dignity of human beings. Nor can a church that is rooted in a God that saves through self-emptying think ofitself as culturally superior to the peoples among whom it works.Mission,as participation in the mission of the triune God can only proceed in dialogue and can only be carried out in humility.